1995
DOI: 10.2534/jjasnaoe1968.1995.59
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Hub Effect of Marine Propeller by Surface Vortex Lattice Method

Abstract: SummaryThe hub effect has been ignored in theoretical or numerical calculations of hydrodynamic characteristics of marine propellers so far. In this paper hub effects of some model propellers are investigated by the surface vortex lattice method (SVLM) for the hub and by the ordinary vortex lattice method (VLM) on the lifting surface for the blade. The surface, where the surface vortex lattices are distributed, is taken inside of the real surface of the hub in order to avoid the strong interference effect betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a research performed in 1992 on controllable pitch propellers it was shown that in addition to the pressure distribution in sections near the blade root the hub also affects the performance of the propeller in open-water condition [5]. According to the results obtained by Liu in 1995, in ordinary hubs of small diameter, which are mainly used in constant pitch propellers and surface ships, the effect of hub on hydrodynamic forces of the propeller such as thrust and torque, is not remarkable [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a research performed in 1992 on controllable pitch propellers it was shown that in addition to the pressure distribution in sections near the blade root the hub also affects the performance of the propeller in open-water condition [5]. According to the results obtained by Liu in 1995, in ordinary hubs of small diameter, which are mainly used in constant pitch propellers and surface ships, the effect of hub on hydrodynamic forces of the propeller such as thrust and torque, is not remarkable [6].…”
Section: Introductionmentioning
confidence: 99%